ZnMgSe:Cr²⁺ — a new active medium for lasers of middle IR - Zagoruiko, Yu.A.; Kovalenko, N.O.; Puzikov, V.M.; Fedorenko, O.A.; Basiev, T.T.; Doroshenko, M.E.; Osiko, V.V.; Jelinkova, H.; Koranda, P. (Functional Materials, 2009)
For the first time, laser generation is obtained in Zn₀.₇₅Mg₀.₂₅Se:Cr²⁺ single crystal. It is established that wavelength tuning in this laser can be realized in 2.2-2.6 μm region. The optical, luminescent and generation characteristics of the new active laser medium are studied and compared with the corresponding characteristics of ZnSe:Cr²⁺ single crystal. Вперше отримано лазерну генерацію у монокристалі Zn₀.₇₅Mg₀.₂₅Se:Cr²⁺. Перестроювання довжини хвилі генерації такого лазера можна здійснювати у діапазоні 2,2- 2,6 мкм. Досліджено оптичні, люмінесцентні та генераційні характеристики нового активного лазерного середовища та проведено їх порівняння з характеристиками монокристалів ZnSe:Cr²⁺. Впервые получена лазерная генерация в монокристалле Zn₀.₇₅Mg₀.₂₅Se:Cr²⁺. Перестройка длины волны генерации может осуществляться в диапазоне 2,2-2,6 мкм. Изучены оптические, люминесцентные и генерационные характеристики новой активной лазерной среды и проведено их сравнение с характеристиками монокристаллов ZnSe:Cr²⁺.